Relationship of personality-academic environment congruence and factors of career decision making among student teachers’ in Public Higher Education Institute (IPTA) - Abdullah, Siti Haswa Niza (2014)
The purpose of this paper to explore the relationship of personality with academic environment congruence of the university student teachers’ toward teaching as a potential career choice are defined.Preliminary findings shows that more environmental factors influence an individual's motives in choosing teaching as a career.However, the tendency of dominant motivation attitude due to personal factors. Nevertheless, the overall findings explain the existence of a significant relationship between personality and academic environment congruence factors influencing the teaching profession.The study found that positive student teachers to the concept of congruence will make them active in the system environment of academic activities.At the end of the discussion proposed some suggestions to improve the congruence to promote an academic environment that is conducive and effective in producing quality teachers and will remain in the teaching profession.